The presence of Mycoplasma pneumoniae infection and GM1 ganglioside antibodies in Guillain-Barré syndrome - Mridula B Sharma; Rama Chaudhry; Irum Tabassum; Nishat Hussain Ahmed; Jitendra Kumar Sahu; Benu Dhawan; Veena Kalra (Journal of Infection in Developing Countries)
Introduction: Guillain-Barré syndrome (GBS) is an autoimmune disorder affecting the peripheral nervous system, usually triggered by an acute infection. GBS patients are known to have antecedent bacterial infections associated with auto-antibodies to various gangliosides. This investigation aimed to evaluate GBS patients for serological evidence of Mycoplasma pneumoniae infection and anti GM1 ganglioside antibodies.